Monoclonal antibodies to the glycoprotein of vesicular stomatitis virus: comparative neutralizing activity. - Volk, W A (1982)
Nineteen independently isolated hybridomas producing monoclonal antibodies to the glycoprotein of vesicular stomatitis virus were isolated and studied for their capacity to neutralize viral infectivity. By measuring competitive binding of 125I-labeled monoclonal antibodies in a radioimmunoassay. 11 different, non-cross-reacting antigenic determinants were identified on the vesicular stomatitis virus G protein. All monoclonal antibodies reacting with determinants 1, 2, 3, and 4 resulted in viral neutralization, whereas those binding to the other seven determinants did not neutralize infectivity. The mixture of two monoclonal antibodies binding to different determinants resulted in a more rapid neutralization than either antibody alone, suggesting that different antibodies can exert a synergistic effect on viral neutralization. Kinetic experiments revealed biphasic neutralization curves similar to those expected for heterologous antibody. No evidence could be obtained to relate biphasic kinetics of viral neutralization to heterogeneous populations either of antibody molecules or of virus. The possible significance of the kinetic data with monoclonal antibodies is discussed.